A study on influence of process parameters on the SIS processability and mechanical properties of a HDPE. (2018) - Baligidad, Sagar M; Chandrasekhar, U; Elangovan, K; Shankar, S; Anjankumar, N; Supriya, J
Abstract: Selective Inhibition Sintering (SIS) is emergent rapid prototyping technology that builds the solid parts by fusing the powder particles layer by layer with heat, directly from CAD model. The SIS process has many processing parameters of which some have a direct effect on the mechanical properties of the parts fabricated. The HDPE powder particle size was characterized by scanning electron microscopy, differential scanning calorimetry and particle size analysis. This work shows feasibility of processing an HDPE by SIS process. The effects of SIS process parameters like layer thickness, heater power and heater feed rate on tensile properties of HDPE samples are investigated. To obtain the mechanical properties, the samples were submitted to tensile testing. A thermal consequence on the mechanical properties of HDPE parts fabricated by inhibition sintering process is also discussed